A gonadotropin-releasing hormone antagonist reduces serum adrenal androgen levels in prostate cancer patients - Yoshiyuki Miyazawa; Yoshitaka Sekine; Takahiro Syuto; Masashi Nomura; Hidekazu Koike; Hiroshi Matsui; Yasuhiro Shibata; Kazuto Ito; Kazuhiro Suzuki (BMC Urology, 2017)
Abstract Background Adrenal androgens play an important role in the development of castration-resistant prostate cancer therapeutics. The effect of gonadotropin-releasing hormone (GnRH) antagonists on adrenal androgens has not been studied sufficiently. We measured testicular and adrenal androgen levels in patients treated with a GnRH antagonist. Methods This study included 47 patients with histologically proven prostate cancer. All of the patients were treated with the GnRH antagonist degarelix. The mean patient age was 73.6 years. Pre-treatment blood samples were collected from all of the patients, and post-treatment samples were taken at 1, 3, 6, and 12 months after starting treatment. Testosterone (T), dihydrotestosterone (DHT), dehydroepiandrosterone (DHEA), 17β-estradiol (E2), and androstenedione (A-dione) were measured by liquid chromatography-mass spectrometry. Dehydroepiandrosterone-sulfate (DHEA-S), luteinizing hormone, and follicle-stimulating hormone levels were measured by electro-chemiluminescence immunoassays. Results A significant reduction in T level (97.3% reduction) was observed in the patients 1 month after initiating treatment. In addition, levels of DHT, E2, DHEA-S, and A-dione decreased 1 month after initiating treatment (93.3, 84.9, 16.8, and 35.9% reduction, respectively). T, DHT, E2, DHEA-S, and A-dione levels remained significantly suppressed (97.1, 94.6, 85.3, 23.9, and 40.5% reduction, respectively) 12 months after initiating treatment. A significant decrease in DHEA level (15.4% reduction) was observed 12 months after initiating treatment. Conclusions Serum adrenal androgen levels decreased significantly in patients treated with a GnRH antagonist. Thus, long-term GnRH antagonist treatment may reduce serum adrenal androgen levels.